A New Perspective on Education in the Digital Age Teaching, Media and Bildung - Tække, Jesper (Bloomsbury Academic, 2021)
Drawing together action-based research with sociology of education, medium theory and the Bildung-tradition, the authors offer a new perspective on education in the digital age, exploring emancipation, edification, self-formation and democratic education. The authors draw on 15 years of action-based research and weave this with the theory to show how teachers and students might use new media for learning about interaction, searching, visualizing, constructing, storing, and retrieving. The authors show that education needs to be rethought, resituated and developed anew in the digital age. New norms and new ways of teaching need to be established. Building on the theory and case studies, they analyze and discuss different strategies, ideas and understandings, offering four promising ways to develop a new vision for education. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com. Open access was funded by Aarhus University.